2013
DOI: 10.1016/s2221-1691(13)60069-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult female of Strongyloides stercoralis in respiratory secretions

Abstract: The presence of adult female S. stercoralis which has never been observed before in the clinical samples submitted to our Laboratory for investigation can be considered as an indirect marker of the severe immunosupression of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
1
0
2
Order By: Relevance
“…The authors concluded that the presence of adult female S. stercoralis in clinical samples can be considered as an indirect marker of severe immunosuppression. [ 11 ] The presence of eggs of S. stercoralis in respiratory secretions obtained from an AIDS patient was also reported by Bava and Troncoso. [ 12 ]…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors concluded that the presence of adult female S. stercoralis in clinical samples can be considered as an indirect marker of severe immunosuppression. [ 11 ] The presence of eggs of S. stercoralis in respiratory secretions obtained from an AIDS patient was also reported by Bava and Troncoso. [ 12 ]…”
Section: Discussionsupporting
confidence: 55%
“…[ 10 ] Bava et al . [ 11 ] first reported the presence of adult female and eggs of S. stercoralis in respiratory secretions obtained from an HIV-negative patient who had polymyositis and was on a treatment with corticosteroids. The authors concluded that the presence of adult female S. stercoralis in clinical samples can be considered as an indirect marker of severe immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…O conjunto de sintomas pulmonares causados pela migração de larvas para os pulmões tais como a tosse seca, dispneia, crises asmatiformes, hemorragia alveolar e edema pulmonar caracterizam a Síndrome de Loefler (MUKERJEE et al, 2003;VIJAYAN, 2009;BAVA et al, 2013).…”
Section: Sintomatologia Da Estrongiloidíase Humanaunclassified
“…A triagem de pacientes assintomáticos para a infecção por Strongyloides é importante para prevenir a síndrome de hiperinfecção. Entre os testes disponíveis, os testes imunológicos são confiáveis em populações de áreas endêmicas e não endêmicas (KEISER; NUTMAN, 2004;BAVA et al, 2013).…”
Section: Diagnóstico Da Estrongiloidíaseunclassified